Which investors' characteristics are beneficial for initial coin offerings? Evidence from blockchain technology-based firms - Christian Hackober; Carolin Bock (Journal of Business Economics, 2021)
Initial coin offerings have recently become one of the most important funding resources for ventures in the blockchain area. However, often ventures do not rely solely on initial coin offerings as funding source but receive also investments from more established investors prior or during their initial coin offering. In particular, blockchain related ventures have drawn the attention of (corporate) venture capitalists but only less is known on the interplay of these different funding sources and their influence on initial coin offerings as well as on ventures' further development. Based on the signaling theory as well as the resource-based-view our empirical study find that venture capital investors as well as corporate venture capital investors have a significantly positive effect on initial coin offerings. Further, we find that the reputation, the time of treatment as well as the specialization of investors have a positive influence on the initial coin offering. Finally, our results indicate that the positive effect of venture capital investors as well as the specialization of an investor continues to influence blockchain based ventures' success in the mid-term.
Keywords: G10; G20; G24; G32; D82; L26; O30; 650; Blockchain; ICO; Venture capital; Corporate venture capital; Cryptocurrency; Distributed ledger; Digital tokens